2012
DOI: 10.1111/infa.12001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seeing and Hearing Vowels on Neonatal Facial Imitation

Abstract: For several decades, many authors have claimed the existence, early in life, of a tight link between perceptual and productive systems in speech. However, the question whether this link is acquired or is already present at birth remains open. This study aimed at investigating this question by employing the paradigm of neonatal facial imitation. We compared imitative responses of newborn infants presented either visual‐only, audiovisual congruent, or audiovisual incongruent models. Our results revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 44 publications
3
39
0
2
Order By: Relevance
“…From these findings, Yeung and his colleagues have proposed that the information available in auditory and visual speech is mapped onto a common articulatory representation (48). This interpretation is also supported by vocal imitation studies in preverbal infants (8,(49)(50)(51), as in all of these studies the infants had access to both the auditory and visual information in speech. However, such findings (i) do not address, or consider, the extent to which sensorimotor information influences the perception of auditory speech directly, without visual support, and (ii) cannot rule out the possibility that experience with the native language has played a role in establishing specific sensorimotor influences on speech perception.…”
Section: Discussionmentioning
confidence: 89%
“…From these findings, Yeung and his colleagues have proposed that the information available in auditory and visual speech is mapped onto a common articulatory representation (48). This interpretation is also supported by vocal imitation studies in preverbal infants (8,(49)(50)(51), as in all of these studies the infants had access to both the auditory and visual information in speech. However, such findings (i) do not address, or consider, the extent to which sensorimotor information influences the perception of auditory speech directly, without visual support, and (ii) cannot rule out the possibility that experience with the native language has played a role in establishing specific sensorimotor influences on speech perception.…”
Section: Discussionmentioning
confidence: 89%
“…This latter result shows that even if infants have not yet seen their tongue (or other facial gestures) they recognize the recruited effector as well as the associated action and correctly match it with an appropriate imitation. Therefore, developmental research suggests that experience-dependent associative mechanisms cannot account for multisensory association effects in general (Meltzoff & Borton, 1979;Meltzoff & Moore, 1977), and during audiovisual speech processing (Coulon, Hemimou, and Streri, 2013).…”
Section: The Role Of Experience In Building Sensorimotor Speech Mapsmentioning
confidence: 99%
“…For instance, Yeung and Werker (2013) found that 4.5-month-old infants looked longer at the speaker's lip movements which did not correspond to the shape of their own lips (e.g. It is important to acknowledge, however, that whilst production influences perception, the opposite can also occur: that is, audiovisual speech perception influences vocal production (Chen et al, 2004;Coulon et al, 2013;Kuhl & Meltzoff, 1982, 1996Legerstee, 1990;Patterson & Werker, 1999). This indicates that a concurrent motor task can perturb an audiovisual matching task.…”
Section: Introductionmentioning
confidence: 99%